Field sampling methods for remedial investigations - Byrnes, Mark E. (CRC Press, 2009)
Of major environmental laws and regulations -- Designing a defensible sampling program -- Field investigation methods -- Sample preparation, documentation, and shipment -- Quality control sampling -- Data verification and validation -- Data quality assessment -- Equipment decontamination -- Health and safety -- Management of investigation-derived waste.